Models of tax incentives for R&D activities of enterprises in European Union countries - Szlęzak-Matusewicz, Joanna (Copernican Journal of Finance & Accounting, 2014)
An aim of the author’s considerations contained in the article is to describe the models of tax incentives supporting research and development activity carried out by enterprises in European Union countries, with a particular consideration of Polish solutions as well as their attractiveness from the enterprises’ point of view. To achieve the objectives there were analyzed reports and surveys conducted by international organizations as well as presented the generosity level of tax incentives in different countries. There is also evaluation of Polish legal regulations supporting R&D activities, pointing out the potential directions of change in tax law.